Exploring Teachers’ Experiences on the Construction and Use of Teaching Materials in Mathematics Classroom: A Narrative Inquiry - Basnet, Lok Bahadur (Journal of Mathematics Education, 2023)
Teachers' experience and knowledge with the construction and use of teaching materials influences the teacher's classroom activities. This study intended to explore mathematics teacher's experience on the construction and use of teaching materials in the classrooms. This study used a narrative inquiry approach to explore the use and construction of teaching materials in mathematics teaching, focusing on the experiences of mathematics teachers from secondary schools in Dang district of Nepal. The findings suggest that the experienced mathematics teachers used only text-books and whiteboards as teaching materials. They did not use additional teaching materials in their mathematics classrooms at the beginning of their careers. Further, with the help of in-service teacher training, the research participants got the knowledge and skills to construct and use teaching materials, like the prism models, pyramids, cones, and cylinders. Furthermore, the findings also suggested that the teachers do not use these teaching materials regularly due to poor classroom management and overwork load. The findings of this study can be helpful for mathematics teachers, teacher trainers, school administrations, and policymakers for meaningful mathematics teaching and learning.